Superhydrophobic nanocontainers for passive and active corrosion protection - Zhao, Yue; Xu, Teng; Zhou, Jin-He; Hu, Ji-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Superhydrophobic nanocontainer strategy was proposed for anticorrosion.•Superhydrophobic metal organic framework (MOF) nanocontainer was synthesized.•Superhydrophobic MOF has better compatibility with polyvinyl butyral (PVB) resin.•Superhydrophobic nanocontainer provides reduced water absorption.•The superhydrophobic property ensures slower release rate of inhibitors. A superhydrophobic metal organic framework (MOF) nanocontainer strategy, other than conventional hydrophilic MOF nanocontainer process, was proposed for anticorrosion. Compared with the hydrophilic nanocontainers, the superhydrophobic MOFs have better compatibility with polyvinyl butyral (PVB) resin and provide reduced water absorption of the composite coating. In addition, the superhydrophobic property ensures slower release rate of encapsulated inhibitors from the nanocontainers. Thereby, the corrosion resistance of the PVB coating on copper substrates embedded with superhydrophobic MOF nanocontainers pre-loaded with 2-Amino-5-mercapto-1,3,4-thiadiazole (AMT) has been significantly improved. The molecular dynamics simulation was applied to understand the experimental results.